Winners, Losers, and Facebook: The Role of Social Logins in the Online Advertising Ecosystem - Krämer, Jan; Schnurr, Daniel; Wohlfarth, Michael (Management Science, 2019)
Social logins, such as “Log in with Facebook,” improve a website’s user experience and therefore enjoy great popularity among content providers (CPs) and users alike. Moreover, they also enable the social network and the CPs to share data, which individually improves their ability to place targeted advertising. On the basis of a game-theoretic model that offers a microfoundation for CPs’ competition for advertisements, on the one hand, and CPs’ competition for users, on the other hand, we demonstrate the strategic effects of social logins in the online advertising ecosystem. We fully characterize the market conditions under which social logins are offered and adopted, and when the adoption is actually profitable for the CPs. In particular, we show across several model extensions that the voluntary adoption of the social login may yield a prisoner’s dilemma outcome for the CPs. The online appendix is available at https://doi.org/10.1287/mnsc.2017.3012 . This paper was accepted by Chris Forman, information systems.